Could NQO1 genotypes impact the results of clinical trials with idebenone? - Valerio Carelli; Martina Romagnoli; Filippo Fortuna; Claudio Fiorini; Leonardo Caporali; Thomas Klopstock; Chiara La Morgia; Anna Maria Ghelli (Brain, 2026)
Carelli et al. argue that new insights into how NQO1 influences the response to idebenone warrant reevaluating the results of previous clinical trials, including those in Friedreich ataxia and Duchenne muscular dystrophy, using patient stratification by NQO1 genotype.